Incidence of the non-application of the principle of reasonable time in the inefficiency of the preparatory investigation stage in cases of preventive detention in the fiscal district of Tacna 2013-2014. - Arcaya Pancca, Diana Beatriz (2016)
Objective: The objective of the present investigation was to determine the incidence of non-application of the principle of Reasonable Term in the inefficiency of the Preparatory Investigation Stage in cases ofpretrial detention in the Fiscal District of Tacna, period 2013- 2014. Material and method: The hypothesis of study was: In the Fiscal District of Tacna the nonapplication of the principle of Reasonable Term significantly influences the inefficiency of the Preparatory Investigation Stage in the cases of preventive detention, period 2013-2014. The type of research ¡is Applied. The study correspondsto the non-experimental design (ex post facto). Likewise, it corresponds to a Descriptive-Explicative design. From the geographic point of view this research work is departmental, since the study includes the cases of preventive detention in the Fiscal District of Tacna. For this purpose, the information obtained through the application of the questionnaire, interview cards and the analysis sheet were considered; As instruments of measurementof the variables to be studied. Results: Once the phase of analysis and interpretation of the results was completed, it was specified that: a) At the stage of Preparatory Investigation in cases of pre-trial detention, it is not possible to apply the Reasonable Term Principle, taking into account the specific needs of the investigation , In the Tax District of Tacna, period 2013-2014; b) The stage of Preparatory Investigation in cases of preventive detention, in the Tax District of Tacna, period 2013-2014, is inefficient, thus proving the research hypothesis. Conclusion: In the stage of Preparatory Investigation in cases of pre-trial detention, it is imperative to apply the principle of Reasonable Term, taking into account the specific needs of the investigation, in the Fiscal District of Tacna during the years 2013-2014.